Analysis of Operational Management Functions of MSMEs in Indonesia - ., Basrowi; Meida, Evi (American Journal of Social Sciences and Humanities, 2019)
The purpose of this research is to analyze: a) the value of micro small and medium enterprises (MSMEs) Product “Bata Merah (Red brick), the creation of new products “Bata Merah”, and the development system that has been carried out by MSMEs actors; and b) the organizing system for the development of “Bata Merah”, and the design of processes (transformation) for making “Bata Merah”. The method used is a case study, with a qualitative approach. research conducted in MSMEs Lampung Province Indonesia. Based on the results of the analysis it can be concluded: 1) The product development system can be done by increasing the quality of raw materials, quality of the dough, and so on. 2) Organizing product development starts from organizing workforce and division of tasks according to their respective roles. The operational management function in the MSMEs has been well implemented, ranging from operational planning, operational scheduling, to operational supervision.